Markets and the Meaning of Flexibility - William A. Jackson (Economic Issues, 2015)
Markets are reputed to be more flexible than other economic arrangements, though the meaning of flexibility remains vague. For orthodox economists, it has a narrow interpretation based on relative price movements within equilibrating markets, leading to allocative efficiency. For heterodox economists and other social scientists, it goes beyond market-clearing equilibrium to take in price setting, non-price adjustments and the institutional background. This paper examines the meaning of flexibility as applied to markets and evaluates the main alternative views. The orthodox approach, which informs most economic commentary, offers a deceptive story of a complete market system with rapid price changes. Actual economies are flexible not through prices alone but through various adjustment methods.
Keywords: B52; D40; L10; 330; markets; flexibility; price setting; relational trade; economic evolution